Attributional style in depressive and anxiety disorders - Lauri Korajlija, Anita; Jokić-Begić, Nataša; Jurin, Tanja (2009)
Introduction: Attribution theories consider that individual's attributional style affects the likelihood of emotional difficulties occurring and their intensity and duration. Attributional theories of depression assume that negative attributional style influences the occurrence of depression ; while its severity determines the intensity and maintenance of depression. Objectives: The aim of research was to examine the attributional theory postulates in depression and anxiety disorders. Methods: Research was conducted on the convenient sample of 81 patients divided into two groups, a group of patients with clinical depression (N = 40) and a group of patients with clinical anxiety (N = 41) and 43 control group participants equalized by gender and age. The following questionnaires were applied: Beck’ s Depression Inventory, State-Trait Anxiety Inventory, and Attributional Style Questionnaire. Results: The results show that negative attributional style is expressed the most in depressive participants, while it is expressed the least in the control group participants. Anxiety and control group participants showed more positive than negative attributional style. These results are consistent with previous findings, which state that a negative attributional style is associated with depression, but not with anxiety. Participants of all three groups vary in attributional style expressed in negative events, with negative attributional style being more expressed in depressive and anxious participants. Positive events are attributed to internal, stable and global controllable factors by participants of all three groups, but the control group participants were prone the most to such attributions. Negative attributional style is poorly but significantly associated with depression (r = 0.20, p <0.05). Conclusion: Based on the obtained results we can determine that a negative attributional style has a role in the occurrence but not in the severity of depression disorder.
Projekt MZOS
ENG